Water cascade analysis technique for minimum flowrate targeting: tabular and numerical approach - Foo, Dominic Chwan Yee; Abdul Manan, Zainuddin; Abdul Aziz, Ramlan (Universiti Malaysia Sabah, 2003)
This work presents the Water Cascade Analysis (WCA) as a new technique to establish the minimum water and wastewater targets for continuous water-using processes. The WCA is a numerical alternative to the graphical water targeting technique known as water surplus diagram. The WCA is to the water surplus diagram in water pinch analysis as a problem table analysis is to the grand composite curves in heat pinch analysis. By eliminating the tedious interactive steps of the water surplus diagram, the WCA can quickly yield accurate water targets and pinch point locations for water network, thereby offering a key complimentary role to the water surplus diagram in the design and retrofit of a water recovery network. As in the case of the water surplus diagram, the WCA is not limited to mass transfer based operations and is applicable to a wide range of water using operations.